Incorporating Cattle Manure Improves Hydraulic Properties and Enhances Infiltration Rates of Low‐Infiltrability Saline‐Sodic Soils - Li, Xia; Guo, Zhengxiong; Ma, Yulei; Leite, Pedro A. M.; Li, Zhigang; Wu, Gao‐Lin (Land degradation & development, 2025)
ABSTRACT Drylands present a significant challenge to global agricultural production, especially in dryland saline‐sodic soils, which are marked by poor structure and low infiltrability. Enhancing the infiltration capacity of these soils is crucial for enhancing soil health and optimizing land‐use efficiency. However, few studies have been conducted to improve soil physical structure and enhance water infiltration and storage capacity in saline‐sodic soils through agricultural waste. This study aims to evaluate the effectiveness of cattle manure amendments in improving water infiltration and related soil properties in dryland saline‐sodic soils. Our results show that mixing cattle manure into the topsoil soil significantly enhances infiltration rates, with the initial and the stable infiltration rates increasing on average by 64.5% and 52.1%, respectively, over the three‐year study period. These improvements are associated with a reduction in bulk density and soil compressive strength by 6.9% and 101.9%, respectively, as well as increases in total porosity, non‐capillary porosity, and soil organic matter by 6.6%, 24.7%, and 8.7%, respectively. In contrast, cattle manure mulching in the topsoil has no significant impact on infiltration and soil properties. Structural equation models reveal that soil water content, non‐capillary porosity, and total porosity are the primary properties influencing the stable infiltration rates, whereas total porosity, soil compressive strength, and non‐capillary porosity are key factors affecting the initial infiltration rate. Our findings demonstrated that incorporating cattle manure into the soil can effectively enhance the soil porosity properties, infiltrability, and organic matter content of saline‐sodic soils. These findings highlight the potential of cattle manure to improve soil physical properties and enhance water infiltration in low‐infiltrability saline‐sodic soils, offering a theoretical basis for addressing this issue in semiarid regions.